Travel History: Reconstructing Travelers Semantic Trajectories based on Heterogeneous Social Footprints - Santana, Amon Veiga; Campos, Jorge (Journal of Information and Data Management, 2017)
Travel specialized websites have increased their sociability and usage by adopting mechanisms that facilitates content sharing in real time between users. These web applications, however, lack tools that allow travelers to share their experiences, such as places they have visited, itineraries they have performed, and other activities of a typical touristic trip. These kinds of information, when available, are insufficient and incomplete. The process of generating structured and semantic rich datasets based on recommended trips, routes and destinations usually requires high effort to be generated. This task is frequently manual, cumbersome, inaccurate, time-consuming, and depends on user ́s willingness to cooperate. This work proposes a solution for reconstructing travel histories using heterogeneous social sources, such as posts in social networks, GPS positioning data, location history data generated by cloud services or any digital footprint with an associated geographic position. The solution encompasses a conceptual model; a methodology to reconstruct travel histories based on heterogeneous social tracks sources; and an application to present the reconstructed travel itinerary in a graphical and interactive fashion. An experiment conducted with real travelers showed that the proposed solution is a reasonable way to reconstruct semantic-rich travel histories in an automatic fashion